2008
DOI: 10.13031/2013.24148
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fecal/Ingesta Contaminants on Poultry Processing Equipment Surfaces by Visible and Near-Infrared Reflectance Spectroscopy

Abstract: ABSTRACT. Visible and near-infrared (NIR) o ensure a wholesome and safe meat supply for consumers, the USDA Food Safety and Inspection Service (FSIS) has established policies for meat and poultry processing in order to minimize the risks of bacterial pathogens in meat and poultry products (USDA, 1994). More recently, FSIS implemented Pathogen Reduction, Hazard Analysis, and Critical Control Points (HACCP) programs, which hold processing plants accountable to detailed standard operating procedures developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…All faecal samples collected in this study showed a similar profile and trend. Two distinct bands were observed around 576 and 670 nm, which had been found previously to be associated with Hb and chlorophyll, respectively [ 42 , 51 , 52 ]. Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387–609 nm to limit the effects of the 670-nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 81%
“…All faecal samples collected in this study showed a similar profile and trend. Two distinct bands were observed around 576 and 670 nm, which had been found previously to be associated with Hb and chlorophyll, respectively [ 42 , 51 , 52 ]. Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387–609 nm to limit the effects of the 670-nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 81%
“…All faecal samples collected in this study showed similar pro le and trends. Two distinct bands were observed around 576 nm and 670 nm, which were previously found to be associated with Hb and chlorophyll, respectively (41,49,50). Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387-609 nm to limit the effects of the 670 nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 83%
“…All faecal samples collected in this study showed similar pro le and trends. Two distinct bands were observed around 576 nm and 670 nm, which were previously found to be associated with Hb and chlorophyll, respectively [42,51,52]. Subsequently, for the prediction of Hb in sheep faeces in the present study, all analyses were carried out within the wavelength range of 387 -609 nm to limit the effects of the 670 nm chlorophyll peak.…”
Section: Resultsmentioning
confidence: 83%